MENINGKATKAN KEMAMPUAN MEMAHAMI PERKALIAN CARA SUSUN DENGAN METODE DEMONTRASI PADA SISWA KELAS IV SD NEGERI 10 LAKUDO - Diana, Diana (Gema Pendidikan, 2022)
This study aims to improve students' mastery of multiplication of stacking methods, improve the learning process of Mathematics subjects and improve learning outcomes of Class IV students of SD Negeri 10 Lakudo. A total of 24 students consisting of 16 boys and 8 girls with an average age of 9-10 years with the economic condition of the parents of middle and lower students whose parents work mostly fishermen and live not far from school. Of the 24 students involved in this study, which was carried out in two cycles with the steps in cycle I, namely conditioning students, appreciating, explaining learning materials, asking questions, conducting and checking evaluations, and providing follow-up. While in the second cycle, the steps were conveying learning objectives, conditioning students to appreciate, explaining learning materials through question and answer, giving opportunities to ask questions, providing reinforcement, carrying out evaluations and providing follow-up. The results obtained in the first cycle are 12.5% good qualifications, 33.33% moderate and 54.17% less, while in the second cycle evaluation results obtained are 83.33% of students in good category and 16.67% in moderate category. The results of this study indicate that learning that is carried out using the stacking method using matchstick media as a tool for the process of adding numbers in the multiplication technique of stacking can improve students' understanding of multiplication